Patients' characteristics and the quality of the therapeutic alliance in family‐based treatment and individual therapy for adolescents with anorexia nervosa. (8th March 2013) - LoTempio, Elizabeth; Forsberg, Sarah; Bryson, Susan W.; Fitzpatrick, Kathleen Kara; Le Grange, Daniel; Lock, James
Abstract : This study examines the relationship between patients' characteristics and the therapeutic alliance in family‐based therapy (FBT) and adolescent focused therapy (AFT) for adolescents with anorexia nervosa (AN). Independent observers rated audiotapes of therapy sessions using the working alliance inventory‐observer version (WAI‐o). Patients' characteristics examined to predict the development of the therapeutic alliance included their socioeconomic characteristics, markers of eating disorder psychopathology and expectancy of their treatment. Baseline scores on the eating disorder examination (EDE) were positively correlated with the alliance early in treatment in FBT but no patients' characteristics were correlated with the alliance in AFT. EDE was a moderator of alliance, with higher baseline EDE scores predicting higher alliance scores in the FBT group than in the AFT group. The results suggest that the therapeutic alliance can be successfully developed with adolescents with AN, even those initially reporting high levels of symptomatology. Adolescents' acknowledgement of their symptoms may be an important factor in their ability to develop an alliance with the therapist. Practitioner points: Despite common clinical impressions, it is possible to form a strong therapeutic alliance with adolescents with AN in both family and individual therapy. Adolescents' own reports and perceptions of their eating disorder may be an important factor in their ability to build the therapeutic alliance. Clinical strategies hypothesized to promote a strong therapeutic alliance include the externalization of AN, decreasing blame and a focus on adolescent developmental issues.